Pengaruh Sistem Rekrutmen Pendidik dan Tenaga Kependidikan Terhadap Mutu Pendidikan Yayasan Pendidikan dan Sosial Pondok Pesantren Al-Fadl Banyuwangi - Abdi Fauji Hadiono; Isti Faiyatul Inayah (Institut Agama Islam Darussalam Blokagung, 2020)
The objectives of this research are (1) to examine the implementation of the recruitment system for educators and education personnel, (2) to examine the quality of education that has been achieved by the Education and Social Foundation of the Al-Fadl Banyuwangi Islamic Boarding School (3) to determine the effect of the recruitment system for educators and education personnel on education quality of the Education and Social Foundation of the Al-Fadl Banyuwangi Islamic Boarding School (4) to determine how much influence the recruitment system for educators and education personnel has on the quality of education. This research uses descriptive quantitative method. The population in this study were all educators and educational staff at the Al-Fadl Tegaldlimo Banyuwangi Education and Social Foundation, with a sample of 35 employees. Data collection techniques include observation, questionnaires and documentation. To measure the research variables used the product moment correlation formula. After analyzing the data, it is known that the results of r count = 0.697 if one consults the 5% significance level price for the number of respondents (N) 35-2 = 33 indicates 0.344. So it can be said that rcount is greater than rtable or 0.697> 0.344. The magnitude of the influence of the teacher recruitment system on the quality of education at the Al-Fadl Tegaldlimo Banyuwangi Education and Social Foundation is based on the calculation of the determinant coefficient of 49%. This means that the teacher recruitment system and education variables contribute to an increase in the education quality variable by 49% which is between 41% -60%, which is in the Enough category.